2021
DOI: 10.1111/jocs.15303
|View full text |Cite
|
Sign up to set email alerts
|

Valvular complications following the Impella device implantation

Abstract: Background Despite clear clinical benefits, there is limited evidence regarding possible complications of the novel mechanical support device Impella. Aortic and mitral valve regurgitation or injury are rare but potential complications following implantation of the Impella device. Methods To evaluate valvular complications after the Impella device implantation, we have performed a comprehensive search of literature on multiple sites on this topic. Results and Conclusion Ten case reports and one observational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…Placement and use of the Impella device bear potential risks. Risk factors for worse outcomes with Impella include older patients and female gender due to the higher likelihood of severe peripheral vascular disease and smaller arterial anatomy, respectively [ 3 , 4 ]. Additionally, diabetes mellitus and chronic kidney disease are associated with a negative impact on outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Placement and use of the Impella device bear potential risks. Risk factors for worse outcomes with Impella include older patients and female gender due to the higher likelihood of severe peripheral vascular disease and smaller arterial anatomy, respectively [ 3 , 4 ]. Additionally, diabetes mellitus and chronic kidney disease are associated with a negative impact on outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, diabetes mellitus and chronic kidney disease are associated with a negative impact on outcome. According to several review articles and meta-analyses, the most common complications reported are major bleeding requiring blood product transfusion (15-20%), vascular access complications (about 15%), infection (about 13%), hemolysis (about 10%), vascular complications with a need of surgical repair (about 10%), limb ischemia (about 3-7%), stroke (about 4%) and bleeding requiring surgical intervention (about 2%) [ 3 , 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,37,38 Finally, aortic and mitral valve injury can occur during insertion or manipulation of left-sided devices, leading to clinically significant increases in aortic or mitral regurgitation. 39,40…”
Section: Evidence and Clinical Usementioning
confidence: 99%